P142 Src kinase inhibition attenuates neutrophil degranulation without impairing bacterial killing: a possible therapeutic strategy for acute lung injury?. (14th November 2013) - Macfarlane, JG; Ruchaud-Sparagano, MH; Scott, JA; Bulmer, DA; Khan, CMA; Simpson, AJ
Abstract : Background: A key mechanism in the pathogenesis of acute lung injury (ALI) is excessive neutrophil degranulation in response to an overwhelming inflammatory or infective insult. To date, no pharmacological therapy for ALI has proven beneficial. Aim: To investigate our hypothesis that extracellular neutrophil degranulation can be inhibited without necessarily impairing phagocytosis or live bacterial killing. Methods: Whole blood or purified neutrophils from healthy volunteers were pre-treated with a src kinase inhibitor (PP1) or vehicle control, before stimulation with either Phorbol 12-myristate 13-acetate (PMA), cytochalasin B + N-formylmethionyl-leucyl-phenylalanine (fMLP), lipopolysaccharide (LPS), live serum-opsonized Staphylococcus aureus (SA) or Pseudomonas aeruginosa (PA), to induce degranulation. Degranulation was measured in whole blood using CD63/CD66b expression and in purified neutrophils by extracellular release of myeloperoxidase (MPO) and lactoferrin (LTF). Neutrophil phagocytosis of fluorescent killed bacteria, cell viability, apoptosis and bacterial killing (by serial dilution and colony counting) were also measured. All experiments carried out using n = 4–6 healthy volunteers. Results: PP1 pre-treatment using concentrations above 10 μM significantly attenuated primary and secondary granule exocytosis from healthy neutrophils in response to LPS, cytochalasin B/fMLP, SA and PA but not to PMA. The same effect was observed in whole blood assays and in purified neutrophils, both in free suspension and when adhered to tissue culture plastic. PP1 treatment did not increase neutrophil death in response to the stimuli, nor did it significantly alter baseline apoptosis rates. Importantly, PP1 did not impair neutrophil phagocytosis or live bacterial killing of SA and PA. Conclusions: Our study supports our hypothesis and proposes src kinases as an attractive target for anti-inflammatory therapy in conditions such as ALI.